Pengaruh Abu Terbang Batubara Terhadap Timbulnya Gejala Dermatitis Kontak Pada Karyawan Bagian Boiler di PT. Indo Acidatama Tbk, Kemiri, Kebakkramat, Karanganyar - Apriyantri, Anapis Putri; , Tarwaka, PGDip Sc, M.Erg; , Dwi Astuti, SKM., M.Kes (2015)
Occupational contact dermatitis is a skin desease where exposure come from the workplace. The cause of exposure to subtances from outside in the body both of irritan subtance and allergen. PT.Indo Acidatama Tbk, Kemiri, Kebakkramat,Karanganyar using coal as one of fuel for boilers to generate steam wich also produce pollutant such as fly ash which can increase the risk of contact dermatitis. The purpose of this study to know the influence of fly ash to appearance the symptomps of contact dermatitis on the employees boiler in PT. Indo Acidatama Tbk. The method used observational research with cross sectional approach. Techniques of gets the sample using total sampling method with 25 Respondences a consist of 13 employes from boiler and 12 employes from mechanical workshop. The result of this study used the chi-square statistic test showed significant (p 0.006 <0.05), its means there was influence of fly ash to appearance the symptomps of contact dermatitis on the employees boiler in PT. Indo Acidatama Tbk, Kemiri, Kebakkramat, Karanganyar. Based of this study, 62% employes of boiler exposed contact dermatitis. To reduce contact dermatitis risk, workers should use personal protective equipment completely and awareness of employes' personal hygiene.